Base-Stock Level yang Meminimasi Biaya pada Permasalahan Single Order - Tanti Octavia; Felecia .; Grace Natalia (Institute of Research and Community Outreach - Petra Christian University, 2011)
The purpose of this research is to conduct an analysis on demand characteristic and inventory cost which might potentially influence the determination of base-stock level. Appropriate base-stock level will determine the maximum profit and also reduce the stockout cost for fashion products which has high demand uncertainty and single order problem. Case study is applied on a garment company with eight fashion product types that can be classified into short and long lifetime. The effect of coefficient variation, salvage price and stockout cost is analyzed towards profits and base stock level. It can be concluded that demand variability does not affect base stock level, while stockout cost and salvage price does.